The Effect Of Company Size, Profitability, Leverage, And Institutional Ownership On Tax Avoidance With Liquidity As A Moderating Variable In Construction Industry Companies Listed On The Indonesian Stock Exchange For The Period 2018- 2022 - Galingging, Novina (Jurnal Ilmiah Akuntansi Kesatuan, 2024)
Taxes are one of the primary sources of state revenue and are very important in supporting development and financing state expenditure. However, the achievement of tax revenue in Indonesia still needs to be below the average of Asia Pacific countries, partly due to tax avoidance efforts. Some companies use legal loopholes or take illegal actions to minimize taxes payable, such as shifting income abroad. This study analyzes the effect of company size, profitability, leverage, and institutional ownership on tax avoidance, with liquidity as a moderating variable. The sample comprises 64 construction companies listed on the Indonesia Stock Exchange for 2018-2022, with 320 observations. The research model uses Generalised Least Square (GLS) for direct effects and Two Stage Least Square (TSLS) for indirect effects. The  results  showed  that  company  size,  profitability,  and  institutional  ownership  do  not significantly affect tax avoidance, while leverage has a positive impact. In addition, liquidity, as measured by the Current Ratio, does not strengthen the effect of firm size, profitability, leverage, or institutional ownership on tax avoidance.   Keywords: Firm Size; Profitability; Leverage; Liquidity; Institutional Ownership